2017
DOI: 10.5301/hipint.5000510
|View full text |Cite
|
Sign up to set email alerts
|

Does gender influence how patients rate their patient experience after total hip arthroplasty?

Abstract: It is advantageous for orthopaedic surgeons to focus on the PG domains most pertinent to each patient gender post-THA. Focusing efforts based on gender may allow for better patient satisfaction, optimised reimbursements, and improved hospital ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 20 publications
0
40
1
Order By: Relevance
“…With increased government and private sector pressures to reduce costs, increased expenditure from cementless fixation may result unfavorably. 2,3,42 As such, the use of cementless fixation modalities may warrant some bargaining between arthroplasty providers and implant companies to decrease implant costs. This was demonstrated by Elbuluk and Bosco 43 in a continuous series involving 52 revision TKA episodes.…”
Section: Discussionmentioning
confidence: 99%
“…With increased government and private sector pressures to reduce costs, increased expenditure from cementless fixation may result unfavorably. 2,3,42 As such, the use of cementless fixation modalities may warrant some bargaining between arthroplasty providers and implant companies to decrease implant costs. This was demonstrated by Elbuluk and Bosco 43 in a continuous series involving 52 revision TKA episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, patient satisfaction is typically assessed in a self-reported survey format using questionnaire, numerical or Likert scales. The Press Ganey (PG) survey, a validated patient experience evaluation that asks questions about patient's interactions with staff, wait times, and overall assessment of their care, has one question on patient satisfaction that is only relevant to the outpatient visit [3][4][5]. The visual analog scale (VAS) for patient satisfaction, which has been cited as a simple, valid, and reliable method of assessing patient satisfaction, has been used after both THA and total knee arthroplasty (TKA) [6,7].…”
Section: Patient Satisfaction Measurement In Orthopedic Surgerymentioning
confidence: 99%
“…Numerous studies have explored pain management as predictors of patient satisfaction [4,5]. In evaluation of the VAS for patient satisfaction, a high correlation between a patient's pain score and Oxford hip score suggested that pain was one of the most important factors in patient satisfaction [5,6]. Additional studies have also supported this claim, citing pain relief as a critical component of maximizing patient satisfaction after THA [4,[27][28][29].…”
Section: Pain Managementmentioning
confidence: 99%
“…20 Patient-reported outcome measures are increasingly important for patients who expect to return to their baseline activity levels, and to physicians and hospitals with the introduction of the value-based healthcare model. [21][22][23][24][25][26][27] Therefore, the purpose of this study was to perform a short-term, 3-month interim comparative analysis on outcomes between 150 consecutive robotic-arm-assisted and 102 consecutive manual TKA patients. Specifically, we evaluated (1) patient self-reported symptoms, (2) expectations and satisfaction, and (3) functional activities, based on the new Knee Society Scoring System.…”
mentioning
confidence: 99%